2021
DOI: 10.3389/fonc.2021.681781
|View full text |Cite
|
Sign up to set email alerts
|

RNA N6-Methyladenosine in Cancer Metastasis: Roles, Mechanisms, and Applications

Abstract: Cancer metastasis is a symptom of adverse prognosis, a prime origin of therapy failure, and a lethal challenge for cancer patients. N6-methyladenosine (m6A), the most prevailing modification in messenger RNAs (mRNAs) and non-coding RNAs (ncRNAs) of higher eukaryotes, has attracted increasing attention. Growing studies have verified the pivotal roles of m6A methylation in controlling mRNAs and ncRNAs in diverse physiological processes. Remarkably, recent findings have showed that aberrant methylation of m6A-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 161 publications
(342 reference statements)
0
11
0
Order By: Relevance
“…Considering that the methylation modifications could alter the biological function of RNA molecules at the epigenetic stage, we performed a global methylation overview of CRC ( 48 , 49 ). With the help of the MethylMix R package and Wilcox test, we found six methylation driver genes whose methylation levels were significantly negatively correlated with expression in two groups, including CES3, FAM127B, MAP9, PARVB, RLN2, and ZNF548.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that the methylation modifications could alter the biological function of RNA molecules at the epigenetic stage, we performed a global methylation overview of CRC ( 48 , 49 ). With the help of the MethylMix R package and Wilcox test, we found six methylation driver genes whose methylation levels were significantly negatively correlated with expression in two groups, including CES3, FAM127B, MAP9, PARVB, RLN2, and ZNF548.…”
Section: Resultsmentioning
confidence: 99%
“…Abnormal RNA modifications have been detected in a variety of diseases [ 24 , 33 , 34 ]. In particular, studies showed that RNA modification dysregulations could play important roles in cancer initiation, metastasis, prognosis, and responses to therapies [ 23 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Mechanistically, RNA modifications could affect the expression of genes involved in important oncogenic pathways such as the Wnt/β-catenin pathway, the PI3K-Akt-mTOR pathway, the JAK-STAT pathway, the MAPK pathway, the p53 pathway, the Hippo Pathway, etc.…”
Section: Epitranscriptomicsmentioning
confidence: 99%
“…As m6A readers, RNA-binding proteins including YTHDF1/2/3, IGF2BP1/2/3 and HNRNPC recognize and bind to m6A sites. Among these “readers”, IGF2BP1/2/3 are mainly related to RNA stability [ 15 ]. Interestingly, IGF2BPs preferentially recognize and bind to the m6A sites of oncogene MYC in the region of the coding region instability determinant (CRD) [ 16 ], which results in enhanced MYC expression, illustrating IGF2BPs promote tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%